2017
DOI: 10.3390/md15060154
|View full text |Cite
|
Sign up to set email alerts
|

Induction of p53-Independent Apoptosis and G1 Cell Cycle Arrest by Fucoidan in HCT116 Human Colorectal Carcinoma Cells

Abstract: Abstract:It is well known that fucoidan, a natural sulfated polysaccharide present in various brown algae, mediates anticancer effects through the induction of cell cycle arrest and apoptosis. Nevertheless, the role of tumor suppressor p53 in the mechanism action of fucoidan remains unclear. Here, we investigated the anticancer effect of fucoidan on two p53 isogenic HCT116 (p53+/+ and p53−/−) cell lines. Our results showed that inhibition of cell viability, induction of apoptosis and DNA damage by treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 38 publications
0
32
5
Order By: Relevance
“…This finding is consistent with those of previous studies of colorectal and breast cancer cells. 38,39 On the other hand, flow cytometry and Hoechst staining showed that the number of apoptotic cells had increased significantly following fucoidan treatment with increased expression of the pro-apoptotic protein Bax and decreased expression of the anti-apoptotic protein Bcl-2, suggesting that fucoidan-induced apoptosis may be related to the mitochondria. Therefore, increased expression levels of cleaved caspase-3 and caspase-9 expression, as determined by Western blot analysis were consistent with our expectations.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with those of previous studies of colorectal and breast cancer cells. 38,39 On the other hand, flow cytometry and Hoechst staining showed that the number of apoptotic cells had increased significantly following fucoidan treatment with increased expression of the pro-apoptotic protein Bax and decreased expression of the anti-apoptotic protein Bcl-2, suggesting that fucoidan-induced apoptosis may be related to the mitochondria. Therefore, increased expression levels of cleaved caspase-3 and caspase-9 expression, as determined by Western blot analysis were consistent with our expectations.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, the anti-cancer response appears to be a combination of enhanced immune function, regulation of checkpoint inhibitor levels [9,10], and a direct cytotoxic activity on cancer cells such as DU-145 human prostate cancer cells [11]. In pre-clinical colon cancer cell models, fucoidans induced both apoptosis and cell cycle arrest, while the exact mechanism for this effect remains unclear [12,13,14,15]. One suggested mode of action involves fucoidan-induced endoplasmic reticulum (ER) stress that induces apoptotic cancer cell death via the activation of unfolded protein response (UPR) pathways [14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent data indicate that fucoidan triggers G1 phase arrest and apoptosis in HCT116 colon cancer cells through a p53-independent pathway. In particular, it has been suggested that fucoidan is able to enhance p21 expression at transcriptional level in a p53-independent manner (50). IGF-I signaling is strongly associated with cell growth and has a significant role in ribosome biogenesis by regulating the expression of proteins directly involved in the processing of ribosomal subunits and p53-mediated regulation of cell cycle progression (51).…”
Section: Discussionmentioning
confidence: 99%